The Therapeutic Expression of Anger: Emotionally Expressive Writing and Exposure - (:unkn) unknown (My University, 2013)
The following reports on multiple studies in a line of research examining the use of emotionally expressive writing as a means of altering the experiences of state anger and negative affect. This line of research has also sought to develop an iterative economic version of the prisoner's dilemma game as a behavioral measure of changes in state anger. Preliminary studies demonstrated evidence that expressive writing about an angry memory does trigger initial activations of state anger and negative affect but that subsequent repeated writing does lead to reductions in activation of state anger and negative affect. The current study sought to expand upon those prior findings and more adequately test whether or not such reductions in the activation of state anger and negative affect can be attributed to habituation as a mechanism of change. The differential effects of different schedules of writing/exposure were also investigated. The current study reports data from 100 student participants. All participants participated in three study sessions scheduled two to three days apart. Participants were randomly assigned to one of four conditions: A Spaced Exposure Condition in which participants wrote about an angry memory once on each of three participation days. A Massed Exposure with Long Retention condition in which participants wrote twice about an angry memory on the first day, did not write the second day, and wrote again about an angry memory the third day. A Massed Exposure with Brief Retention condition in which participants did not write the first day, wrote twice about an angry memory the second day, and wrote once about an angry memory the final day. And a Neutral Writing Control group in which participants wrote about different emotionally neutral memories on each of the first two days and an angry memory on the final day. All participants played the economic prisoner's dilemma game on the first and last day of participation to examine differences in competitive behavior that may correlate with amount of expressive writing and levels of state anger and negative affect. The results found that expressive writing about an angry memory was consistently effective in triggering an acute increase in state anger and negative affect. There was some evidence of both within session and between session reductions of state anger and negative affect following repeated writing about an angry memory; however, these effects were tenuous and not able to be dissociated from uncontrolled factors occurring with the passage of time. Therefore, the results were unable to demonstrate evidence for habituation as a mechanism of change. The results are not able to provide support for any differential advantage to spaced or massed exposure sessions. The study does not support the use of the economic version of prisoner's dilemma game as a behavioral measure of changes in state anger. The limitations of the study and potential future empirical directions are discussed.
Keywords: Anger; Competitive Behavior; Emotional Expression; Exposure Therapy; Expressive Writing; Prisoner's Dilemma